PEMBINAAN PENINGKATAN ENGLISH CONVERSATION DI PANTAI INDAH SETOKOK - Tomi Arianto (PUAN INDONESIA, 2019)
Setokok island beach is one of representative destinations in supporting the marine tourism area in Batam. The strategic location of Batam, which is close to neighboring Singapore and Malaysia, is a distinct advantage for this island, with many foreign tourists coming and going on vacation. The phenomena found that the coast guards and people around who should be directly involved in communicating with foreign visitors couldn’t hardly communicate using English at all. The impact of that problem would narrow down the opportunity for coast guards to get additional benefits from this strategic situation. Therefore, the community team took the initiative to provide an English conversations training for coast guards, MSMEs, photographer services, managers, and people around the coast. The method taught was in the form of guidance and practice of English conversations according to the needs and conditions of the training participants. The materials given were in the form of greeting, directing, asking and answering questions, asking for clarification, offering, persuading, and daily vocabulary. The results obtained through community service at Pantai Setokok could be seen from the ability of the speaking conversation practice skills, the addition of vocabulary related to the beach, and the motivation of self-confidence using English.